2014
DOI: 10.1200/jco.2014.32.4_suppl.272
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive radical prostatectomy (CRP) in patients with prostate cancer (PCA) and low-volume osseous metastases.

Abstract: 272 Background: Androgen deprivation (ADT) represents the standard treatment in men with prostate cancer (PCA) and osseous metastases. Unlike therapeutic approaches in other solid tumors, RP is usually ignored due to the common view that the biology of the disease is attributed to preexisting metastases. Recently, it has been shown that potentially lethal cancers persist even after neoadjuvant ADT and chemotherapy. We explored the outcome of patients with PCA and low volume skeletal metastases who were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most recently, Heidenreich et al ( 24 ) reported their experience with cytoreductive prostatectomy. They included eighteen patients who were identified to have minimal osseous metastases (equal to or less than three hot spots on bone scan) and the absence of visceral or extensive lymph node metastases.…”
Section: Direct Evidence In Support Of Cytoreductionmentioning
confidence: 99%
“…Most recently, Heidenreich et al ( 24 ) reported their experience with cytoreductive prostatectomy. They included eighteen patients who were identified to have minimal osseous metastases (equal to or less than three hot spots on bone scan) and the absence of visceral or extensive lymph node metastases.…”
Section: Direct Evidence In Support Of Cytoreductionmentioning
confidence: 99%